Taunus-Wetterau-Limes - Dornbusch, Stefan (1999)
[Dt.:] Hier findet man Angaben zu den Spuren des römischen Limes in Mittelhessen. Geschildert werden in Kürze Aufgaben und Funktionen und die Bestandteile des obergermanischen Limes, teilweise mit Bebilderung und glossarisch verlinkten Begriffen. Der Schwerpunkt liegt dabei auf den Spuren im Taunusgebirge und der Wetterau (Wachtürme, Kastelle, Städte und Orte). - [Engl.:] Mentioned are remains of the Roman Limes in Hesse, Germany. In brief, purpose and function of the Upper German Limes are described and the component parts are presented, partly with illustrations and references to a glossary. The main focus is on the archaeological traces of the Roman frontier in the Taunus mountains and in the Wetterau (watchtowers, forts, settlements and other sites).